english - ТЕРЗИЋ, Предраг Р. (Serbian political thought, 2026)
This scholarly paper examines the prospects and strategic significance of cooperation between Serbia and India within the BRICS platform. Special attention is devoted to the economic dimension of cooperation, especially in international politics, economics, trade, finance, and agriculture. The paper aims to highlight the importance of a more balanced global financial architecture. In this context, Serbia’s potential engagement with BRICS through enhanced cooperation with India is presented as an opportunity for both countries, with an emphasis on their cooperation in science, education, and agriculture. In conclusion, the authors explain that Serbia–India cooperation represents a strategic opportunity to strengthen economic sovereignty and foster sustainable development, while contributing to a more equitable and multipolar international order.
Keywords: BRICS; India; Serbia; economic cooperation; international agreements